1985
DOI: 10.1016/0741-5214(85)90098-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of the acute thrombogenicity of the modified human umbilical vein and autologous artery

Abstract: With the aim to evaluate acute thrombogenicity, segments of human umbilical vein grafts (Dardik Biograft, Meadox Medicals, Inc., Oakland, N.I.), nonheparinized, heparin-alcohol-treated, or covalently heparinized, were implanted into the carotid arteries of sheep. Autologous carotid arteries were used as control grafts. Flow was restricted to 25 ml/ min. Accumulation of autologous a2P-labeled platelets was registered at both anastomotic and midgraft regions for 240 minutes. At the end of the perfusion period, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The platelet-rich throm botic film covering the surface was most firmly anchored at the anastomoses. This is consistent with our previous findings [Lan nerstad et al, 1986;Bjorck et al, 1985] and also stresses the problem of constructing a non-thrombogenic anastomotic region. In earlier studies, we have shown that it is pos sible to decrease the thrombogenicily of syn thetic grafts by heparinizing the surface, e.g.…”
Section: Discussionsupporting
confidence: 83%
“…The platelet-rich throm botic film covering the surface was most firmly anchored at the anastomoses. This is consistent with our previous findings [Lan nerstad et al, 1986;Bjorck et al, 1985] and also stresses the problem of constructing a non-thrombogenic anastomotic region. In earlier studies, we have shown that it is pos sible to decrease the thrombogenicily of syn thetic grafts by heparinizing the surface, e.g.…”
Section: Discussionsupporting
confidence: 83%